Desember 2016 EFEKTIVITAS PELAYANAN PELAPORAN SPT MASA BAGI WAJIB PAJAK ORANG PRIBADI DAN BADAN MELALUI LAYANAN DRIVE THRU (STUDI PADA KPP PRATAMA SINGOSARI) - Maya Zukhrifatil Jinan; Bambang Haryadi; Gita Arasy Harwida (InFestasi, 2016)
The purpose of this research is to identifity the effectiveness of monthly tax return reporting activities through the drive-thruservice in KPP Pratama Singosari. The effectiveness was identified by comparing the objective of the drive thru serviceand its achievment since it is enacted. This research used qualitative descriptive method and depth interview, observationand documentation as data collecting method. The results this study indicates that the drive thru service is generallyeffective, however, it does not give asignificant effect for the KPP’s service in term of the monthly tax return reportingservice.